HIV/AIDS Mortality Trends in Lang Son, Vietnam: Insights from a Population-Based Mortality Registration from 2005 to 2018 - Ngoan Tran Le; Linh Thuy Le; Ngan Dieu Thi Ta; Hung Manh Nguyen; Toan Ha (Tropical Medicine and Infectious Disease)
The HIV epidemic remains a major public health issue globally and in Vietnam. This study assesses changes in HIV/AIDS-related mortality rates over time in Lang Son Province, Vietnam, from 2005–2018. We performed a descriptive epidemiological study using a population-based mortality registration system to examine HIV/AIDS-related mortality. HIV/AIDS-related mortality was converted to a crude and adjusted rate per 100,000 person-years using the World Health Organization’s standard population for 2000–2025. The mortality rate ratio and 95% confidence interval were estimated to examine the province’s time trend from 2005 to 2018. The adjusted mortality rate for HIV/AIDS in Lang Son Province was 12.3 and 2.4 per 100,000 for men and women, respectively, with a male-to-female ratio of 5.1. The province experienced a 94% reduction in HIV/AIDS-related deaths between 2005 and 2018. The mortality rate ratio for 2018 compared to 2005 was lower for men (0.056, 95% CI: 0.029, 0.110) than for women (0.080, 95% CI: 0.019, 0.338). The findings show a gradual decline in HIV/AIDS-related mortality rates in Lang Son Province, Vietnam. However, significant gender disparities in mortality remain a major concern, and HIV remains a significant burden. This highlights the urgency for major efforts to prevent HIV transmission and address these disparities to effectively end the HIV epidemic in Lang Son and throughout Vietnam.